2022
DOI: 10.1007/s42235-022-00253-6
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Method Based on Nonlinear Binary Grasshopper Whale Optimization Algorithm for Feature Selection

Abstract: Feature Selection (FS) is considered as an important preprocessing step in data mining and is used to remove redundant or unrelated features from high-dimensional data. Most optimization algorithms for FS problems are not balanced in search. A hybrid algorithm called nonlinear binary grasshopper whale optimization algorithm (NL-BGWOA) is proposed to solve the problem in this paper. In the proposed method, a new position updating strategy combining the position changes of whales and grasshoppers population is e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Abayomi-Alli et al [ 59 ] demonstrated a Bidirectional Long Short-Term Memory (BiLSTM) for the UCI PD dataset, and their model achieved an accuracy of 82.86% with the original data. Fang and Liang [ 60 ] presented the UCI dataset for Parkinson’s disease and optimization algorithms such as Particle Swarm Optimization (PSO), Whale Optimization Algorithm (WOA), Grasshopper Optimization Algorithm (GOA), Binary PSO (BPSO), and Binary GOA (BGOA) compared to the Nonlinear Binary Grasshopper Whale Optimization Algorithm (NL-BGWOA), and the results showed that the NL-BGWOA achieved 91.30% higher than other optimization algorithms. Figure 10 demonstrates the comparative study of the proposed method based on BO-SVM with the mentioned methods based on the same applied PD standard dataset.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Abayomi-Alli et al [ 59 ] demonstrated a Bidirectional Long Short-Term Memory (BiLSTM) for the UCI PD dataset, and their model achieved an accuracy of 82.86% with the original data. Fang and Liang [ 60 ] presented the UCI dataset for Parkinson’s disease and optimization algorithms such as Particle Swarm Optimization (PSO), Whale Optimization Algorithm (WOA), Grasshopper Optimization Algorithm (GOA), Binary PSO (BPSO), and Binary GOA (BGOA) compared to the Nonlinear Binary Grasshopper Whale Optimization Algorithm (NL-BGWOA), and the results showed that the NL-BGWOA achieved 91.30% higher than other optimization algorithms. Figure 10 demonstrates the comparative study of the proposed method based on BO-SVM with the mentioned methods based on the same applied PD standard dataset.…”
Section: Resultsmentioning
confidence: 99%
“… Comparison between the proposed model and the recent approaches [ 56 , 57 , 58 , 59 , 60 ] using the same standard PD dataset. …”
Section: Figurementioning
confidence: 99%
“…These applications can be broken down into three categories: screening, prediction, and diagnosis [7,16]. Combining MAs with FS methods from clinical datasets has resulted in the recent development of diagnostic methods for detecting individuals infected with the COVID-19 [37,100,101]. This paper uses and evaluates the BMCMBO algorithm to predict patients with the COVID-19 using an FS model combined with the KNN classifier.…”
Section: Application Of Bmcmbo Algorithm In Fs For the Covid-19 Diagn...mentioning
confidence: 99%
“…44 Feature selection has been considered as the most important step in data mining; however, most of the optimization models do not undergo balanced search. Thus, Fang et al 45 proposed nonlinear binary grasshopper whale optimization algorithm for solving feature extraction problem in high dimensional data. With the proposed method, the datasets are expressed in iteration by computation of fewer features, resulting in high accuracy and fitness.…”
Section: Introductionmentioning
confidence: 99%